Efektivitas Problem Based Learning Berbasis Deep Learning terhadap Kemampuan Berpikir Kritis pada Pembelajaran IPA SD - Isnaini Yuliana Ekasari; Triana Atika Zulfa (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
Critical thinking ability is an essential skill for elementary school students in solving complex phenomena in science learning; however, in reality, students’ abilities in analysis and evaluation are still relatively low. This study aims to determine the effectiveness of the Problem Based Learning model based on a deep learning approach on students’ critical thinking ability in elementary school science learning. This study employed a quantitative approach with a quasi-experimental type and a posttest-only control group design. The population consisted of all fourth-grade students of SDIT Al-Anis Kartasura totaling 75 students, with class IV A as the experimental class and class IV B as the control class. Data were collected through essay tests and analyzed using descriptive and inferential statistics. The results showed that the average critical thinking ability of students in the experimental class was 81.00 (high category), while the control class was 74.21 (medium category). The hypothesis test showed a significance value of 0.038 < 0.05, indicating that the Problem Based Learning model based on a deep learning approach is effective in improving students’ critical thinking ability.